The corner frequencies, stress drops and apparent stresses of microearthquakes in the betic region (southern spain) - García García, J. M.; Romacho, M. D.; Jiménez, A. (Física de la Tierra, 2002)
A collection of ground motion recordings has been obtained in the period 1988-1990. Data from the Betic region (southern Spain) have been analysed to study the source scaling. This data set includes records of 43 microearthquakes registered by short-period seismic stations of the RSA network, located around the Granada basin. At high frequencies, the spectrum of P and S waves is characterized by a trend of exponential decay, e-πκf. The κ parameter ranges, for all the stations, roughly from 0.01 to 0.04 sec for P-waves and from 0.006 to 0.04 sec for S-waves. Fluctuations were found to be randomly distributed, with no dependence on magnitude. The expected increase of κ versus hypocentral distance is not evident for these data, possibly due to the lack of information for distances greater than approximately 50 km and also the large fluctuations. Measurement uncertainties and high variability among the geomorphological features of the station sites are probably responsible for the observed dispersion. Spectral parameters were automatically determined by the methods of Snoke (1987) and Andrews (1986) and were analysed with respect to the source model of Brune (1970, 1971). The seismic moments (from P- and S- waves) ranged from 5.45x1017 to 1.53x1020 dyne cm. The mean ratio between fc(P) and fc(S) was found to be 1.3. The source radii spanned from 0.13 to 0.4 km and the static stress drop varied from 0.05 to 3.6 bars. Also, we have estimated the parameter ε (Zúñiga, 1993) to investigate possible variations in stress drop mechanism, and we have found a value of 0.6, which may be indicative of a partial stress release.A collection of ground motion recordings has been obtained in the period 1988-1990. Data from the Betic region (southern Spain) have been analysed to study the source scaling. This data set includes records of 43 microearthquakes registered by short-period seismic stations of the RSA network, located around the Granada basin. At high frequencies, the spectrum of P and S waves is characterized by a trend of exponential decay, e-πκf. The κ parameter ranges, for all the stations, roughly from 0.01 to 0.04 sec for P-waves and from 0.006 to 0.04 sec for S-waves. Fluctuations were found to be randomly distributed, with no dependence on magnitude. The expected increase of κ versus hypocentral distance is not evident for these data, possibly due to the lack of information for distances greater than approximately 50 km and also the large fluctuations. Measurement uncertainties and high variability among the geomorphological features of the station sites are probably responsible for the observed dispersion. Spectral parameters were automatically determined by the methods of Snoke (1987) and Andrews (1986) and were analysed with respect to the source model of Brune (1970, 1971). The seismic moments (from P- and S- waves) ranged from 5.45x1017 to 1.53x1020 dyne cm. The mean ratio between fc(P) and fc(S) was found to be 1.3. The source radii spanned from 0.13 to 0.4 km and the static stress drop varied from 0.05 to 3.6 bars. Also, we have estimated the parameter ε (Zúñiga, 1993) to investigate possible variations in stress drop mechanism, and we have found a value of 0.6, which may be indicative of a partial stress release.